Planar Hexacoordinate Beryllium: Covalent Bonding Between s–block Metals - Jin, Bo; Guan, Xiao‐Ling; Yan, Miao; Wang, Ying‐Jin; Wu, Yan‐Bo (Chemistry : a European journal, 2023)
Achieving a planar hypercoordinate arrangement of s‐block metals through covalent bonding with ligands is challenging due to the strong ionicity involved. Herein, we report the first case of a neutral binary global minimum containing a planar hexacoordinate beryllium atom. The central Be atom is coordinated by six active Be atoms, the latter in turn are enclosed by an equal number of more electronegative chlorine atoms in the periphery, forming a star‐like phBe cluster (Be©Be6Cl6). Importantly, the cluster exhibits dynamically stabilized stemming geometrically from the appropriate matching of metal‐ligand size and electronically from adherence to the octet rule as well as possessing a 6σ/2π double aromaticity. Remarkably, energy decomposition analysis‐natural orbitals for chemical valence (EDA‐NOCV) analysis reveals a significant covalent interaction between the ligand and the central metal beryllium atoms, a fact further supported by a large Wiberg bond index. This cluster is a promising synthetic as its excellent electronic, dynamic and thermodynamic stability. Clusters with covalent bonds: To investigate the potential for planar hypercoordination in s‐block metals, we report a planar hexacoordinate beryllium center in the neutral binary Be©Be6Cl6 cluster. This global minimum is dynamic stabilized and displays the 6σ/2π double aromaticity. Interestingly, chemical bonding analysis further highlights a substantial covalent interaction between the ligand beryllium atoms and the central metal beryllium atoms.